2003
DOI: 10.1002/bmc.209
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of carbamazepine and promethazine in rabbits

Abstract: The interaction of carbamazepine and promethazine in rabbits has been investigated. The influence of this interaction on the processes of biotransformation in the liver was revealed. The drugs were administered as single oral doses (100 mg of each drug) as well as simultaneously with an interval of 15 min. The sequence of administration of the drugs was varied. The influence of promethazine on the pharmacokinetics of carbamazepine is expressed by: (a) strong suppression of carbamazepine's level in plasma and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The modifying influence of PMZ is more strongly revealed in the case of (PMZ + CPM), where PMZ enters the organism first. The analogous effect was observed by us on the study of the interaction of PMZ and carbamazepine, which does not possess a first-pass effect (Rukhadze et al, 2003). We previously arrived at the conclusion that PMZ prepares the liver in some way for the capture of carbamazepine on its first pass through the liver; as a result the sharp suppression of carbamazepine content in blood plasma occurs on simultaneous administration of carbamazepine and PMZ.…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…The modifying influence of PMZ is more strongly revealed in the case of (PMZ + CPM), where PMZ enters the organism first. The analogous effect was observed by us on the study of the interaction of PMZ and carbamazepine, which does not possess a first-pass effect (Rukhadze et al, 2003). We previously arrived at the conclusion that PMZ prepares the liver in some way for the capture of carbamazepine on its first pass through the liver; as a result the sharp suppression of carbamazepine content in blood plasma occurs on simultaneous administration of carbamazepine and PMZ.…”
Section: Resultsmentioning
confidence: 56%
“…they represent the constituents of lytic cocktail, which is in widespread in pediatric patients (Mashkowsky, 2000;American Academy of Pediatrics, 1995;Santhanakrishnan, 2000). The interactions of CPM and PMZ with the antiepileptic drug carbamazepine were previously studied (Rukhadze et al, 1999(Rukhadze et al, , 2003. Carbamazepine induces microsomal liver enzymes (Levy and Pitlick, 1982;Eadie and Tyrer, 1983;Kholodov and Yakovlev, 1985).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…A previous animal study of promethazine in rabbits indicated that the drug is an inducer of microsomal enzymes and is itself a victim of CYP induction caused by carbamazepine. 18 Similarly, doxylamine was found to induce hepatic metabolism in mice 19 ; however, to date, there is no published interaction study in humans. On the other hand, CYP2D6 inhibition by diphenhydramine is well documented in the literature [20][21][22] (Table 2).…”
Section: Pharmacokinetic Interactionsmentioning
confidence: 99%
“…For example, patients taking PMT with ketorolac can cause delirium [15]. The character of kinetic curves of promethazine changed substantially and the elimination of PMT in the blood was prolonged under the influence of carbamazepine and chlorpromazine [16,17]. In addition, patients should be warned not consume anything (drugs and foods) containing caffeine at the treatment by PMT, as caffeine will cause increasing of maximum and current concentration of PMT and its prolongation in organism [18], which indicates that the food-drug interaction should be considered in the period of the drugs treatment.…”
Section: Introductionmentioning
confidence: 99%